Phát triển quy trình xác định lượng vết một số thuốc giảm đau trong nước thải bằng hệ thiết bị điện di mao quản xách tay điều khiển tự động - Đức, Lê Minh; Hùng, Phạm Mạnh; Anh, Dương Hồng; Việt, Phạm Hùng (Vietnam Journal of Chemistry, 2016)
In this report, the simultaneous determination of four non-steroidal anti-inflammatory drugs (NSAIDs): ibuprofen, bezafibrate, naproxen, diclofenac in waste water was comprehensively developed. The procedure for analysis of these NSAIDs is including two steps: extraction/trace enrichment by solid phase extraction method and quantitative determination by portable automated capillary electrophoresis (CE) equipment equipped with capacitively coupled contactless conductivity detector (C4D). The optimal background electrolyte was Tris-(hydroxymethyl aminomethane) 36 mM/lactic acid buffer at pH 8 containing cyclodextrine HP-β-CD in order to increase the separation between naproxen and diclofenac. With the optimized condition, the detection limits of target drugs in the extract were in ranged of 0.2-0.4 mg/L. The relative standard deviation of migration time and peak area were found at 0.3-0.5 % and 3.3-4.5 %, respectively. Recoveries of all drugs in de-ion water, tap water and wastewater matrix were in range of 86.7-98.8 %. Keywords. Capillary electrophoresis, automated system, portable, drug, waste water